Redox Booster: 2D Interactive Visual Chemistry Learning - Mohamad Ruzlan, Wan Nur Atikah; Azmi, Muhammad Farhan; Mohd Supian, Jessifa Joanna (Journal of Computing Technologies and Creative Content, 2019)
Chemistry subject for science stream students in Malaysian secondary school is considered as one of the difficult subject to score in SPM. Students are usually less motivated to learn the subject because of difficulties in understanding the concept. The goal of this project is to facilitate the Chemistry learning process in the form of interactive application. This research will focus on areas where students have lack of understanding in the theoretical part of the subject and not able to visualize the experiment processes in class. Research finding indicates that this interactive elearning application is able to provide a better and effective way to help students learn. Additionally, this application was developed to help students to quickly grasp the concept and visualize the process when using the 2D virtual laboratory. Keywords—chemistry; science stream; interactive; e-learning; 2D virtual laboratory